Predicting the determinants of pandemic giving among Muslims in Malaysia using the extended TPB Model via logistic regression / Amal Hayati Ishak ... [et al.] - Ishak, Amal Hayati; Awang, Salwa Amirah; Yahaya, Muhamad Hasif; Sahri, Mardhiyyah; Moidin, Shofiyyah (Universiti Teknologi MARA Selangor, 2023)
This study investigates the influence of seven motivational factors on pandemic giving. As COVID-19 struck, many philanthropic donations were initiated in the form of fundraising, and surprisingly, the collections were enormous, even within a limited timeframe. However, such situation is limitedly researched, albeit it may help to improve the approach and strategies of charity organisations in increasing fund collection. Thus, adopting the Theory of Planned Behaviour (TPB), this study analyses three core components of TPB; attitude, subjective norms and perceived behavioural control, together with another four variables hypothesized to influence giving behaviour; altruism, trust, religiosity and financial wellness. A survey was administered via convenient purposive sampling to test the hypotheses using logistic regression. Findings indicate that cash was the highest option of giving followed by food, manpower, equipment, expertise, and others. Findings also revealed that intention, number of dependents and monthly saving as the best predictor in influencing pandemic giving behaviour among Muslims especially for cash, equipment and expertise giving. Hence, this study suggests charity marketers to focus on strategies that will increase the intention and appropriately target the groups who are willing to contribute.